2022
DOI: 10.1088/2515-7655/ac8dc1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of hard carbon negative electrodes for sodium-ion batteries

Abstract: Practical utilisation of renewable energy from intermittent sustainable sources such as solar and wind relies on safe, reliable, cost-effective, and high-capacity energy storage systems to be incorporated in the grid. Among the most promising technologies aimed towards this application are sodium-ion batteries. Currently, hard carbon is the leading negative electrode material for sodium-ion batteries given its relatively good electrochemical performance and low cost. Furthermore, hard carbon can be produced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 109 publications
2
17
0
Order By: Relevance
“…biowaste-derived hard carbons reported in literature which are in the range of 3.7-4.2 Å. [49] This could be ascribed to the reduction of the disorder degree in the sample due to the addition of graphene as observed in our previous work. [43] The crystallite size along the c-axis (L c ) and the size of the layer planes (L a ) were 13.42 and 64.04 Å, respectively, as calculated by the Scherrer's equation.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…biowaste-derived hard carbons reported in literature which are in the range of 3.7-4.2 Å. [49] This could be ascribed to the reduction of the disorder degree in the sample due to the addition of graphene as observed in our previous work. [43] The crystallite size along the c-axis (L c ) and the size of the layer planes (L a ) were 13.42 and 64.04 Å, respectively, as calculated by the Scherrer's equation.…”
Section: Resultssupporting
confidence: 61%
“…According to Bragg's Law the interlayer distance ( d 002 ) of rGOCOF corresponds to 3.50 Å, which is slightly higher than the graphene interlayered distance in graphite (3.35 Å). It is worth to remark that the interlayer distance of the graphene‐coffee waste hard carbon is slightly lower when compared to other biowaste‐derived hard carbons reported in literature which are in the range of 3.7–4.2 Å [49] . This could be ascribed to the reduction of the disorder degree in the sample due to the addition of graphene as observed in our previous work [43] .…”
Section: Resultssupporting
confidence: 52%
“…[83] Copyright 2016, The Royal Society of Chemistry. e) 23 Na magic angle spinning NMR and EPR spectra of hard carbons at various discharge points. Reproduced with permission.…”
Section: Nanoporesmentioning
confidence: 99%
“…However, the narrow peak centered at g = 2.002 is caused by the formation of metallic sodium. [159] Operando 23 Na ssNMR was used by Stratford et al to provide insight into the sodiation process, and showed that sodium ions are first adsorbed on the carbon surfaces in the sloping region followed by the formation of quasi-metallic clusters at the plateau region (Figure 9d). [83] Au et al used ex situ 23 Na ssNMR and total scattering to study the [162] Copyright 2017, Shanghai Institute of Organic Chemistry, Chinese Academy of Sciences.…”
Section: Nanoporesmentioning
confidence: 99%
See 1 more Smart Citation